Acetylated histones contribute to the immunostimulatory potential of neutrophil extracellular traps in systemic lupus erythematosus. (26th November 2014) - Pieterse, E; Hofstra, J; Berden, J; Herrmann, M; Dieker, J; van der Vlag, J
Summary: In addition to disturbed apoptosis and insufficient clearance of apoptotic cells, there is recent evidence for a role of neutrophils in the aetiopathogenesis of systemic lupus erythematosus (SLE). In response to various stimuli, neutrophils can rapidly release DNA fibres decorated with citrullinated histones and anti-microbial peptides. These structures are referred to as neutrophil extracellular traps (NETs). In addition to apoptotic cell-derived microparticles, these NETs may comprise a further source of autoantigens, able to drive the autoimmune response in SLE. Our group recently identified specific histone modifications occurring during apoptosis that play an important role in the autoimmune response in SLE. In the current study, we evaluated the presence and immunostimulatory potential of these previously identified histone modifications in NETs. Compared to NETs from healthy donors, the histones present in NETs formed by SLE-derived neutrophils contain increased amounts of acetylated and methylated residues, which we previously observed to be associated with apoptosis and SLE. Treatment of neutrophils with histone deacetylase (HDAC) inhibitor Trichostatin A (TSA), prior to induction of NETosis, induced NETs containing hyperacetylated histones, endowed with an increased capacity to activate macrophages. This implies that specific histone modifications, in particular acetylation, might enhance the immunostimulatory potential of NETs in SLE.